YAP Expression is Related to the Aggressive Behavior of Odontogenic Cysts - Uttagomol, Jutamas; Wongviriya, Adjabhak; Chantaramanee, Ariya; Prasitsak, Thanit (European Journal of Dentistry, 2025)
Yes-associated protein (YAP) and Ki-67 are known to be involved in cell proliferation. While their overexpression is associated with aggressive behaviors in oral squamous cell carcinoma (OSCC), their roles in odontogenic cysts have not been thoroughly investigated. Therefore, this study aimed to evaluate the immunohistochemical expression of YAP and Ki-67 in odontogenic cysts.Tissue samples included 12 radicular cysts, 10 dentigerous cysts, 9 odontogenic keratocysts, and 9 normal oral mucosa specimens. Immunohistochemical analysis was conducted both manually and using ImageJ software for comparison.The Kruskal–Wallis, followed by the Mann–Whitney U-test was used to assess the differences in the YAP and Ki-67 immunoexpression levels among various group lesions. The correlation between those two proteins in individual groups was tested by Spearman correlation. A p-value of less than 0.05 was considered statistically significant. SPSS software version 25.0 was used.There was a strong nuclear staining of YAP in basal and superficial cells and an intense cytoplasmic YAP positivity in odontogenic keratocysts, whereas a weaker YAP staining in both the nucleus and cytoplasm throughout the epithelial thickness was observed in dentigerous cyst, radicular cyst, and normal oral mucosa, respectively. YAP expression differed significantly in all odontogenic cysts compared with normal oral mucosa (p < 0.05). Ki-67 expression was notably higher in odontogenic keratocysts relative to other cysts and normal oral mucosa. Although no statistically significant correlation was found between YAP and Ki-67 across the groups, both proteins displayed similar positive trends in odontogenic keratocysts.These findings suggest that YAP activation may be related to the proliferative behavior of odontogenic cysts, especially in more aggressive lesions, but less likely to influence the inflammatory cysts. This insight could improve understanding of their pathogenesis and pave the way for new diagnostic and therapeutic approaches.
Keywords: odontogenic cysts; odontogenic keratocysts; YAP; Ki-67; Yes-associated protein; Immunohistochemistry